RUNX1 deficiency (familial platelet disorder with predisposition to myeloid leukemia, FPDMM) - Schlegelberger, Brigitte (2017)
In this review, we discuss disease-causing alterations of RUNT-related transcription factor 1 (RUNX1), a master regulator of hematopoietic differentiation. Familial platelet disorder with predisposition to myeloid leukemia (FPDMM) typically presents with (1) mild to moderate thrombocytopenia with normal-sized platelets; (2) functional platelets defects leading to prolonged bleeding; and (3) an increased risk to develop myelodysplastic syndromes (MDS), acute myeloid leukemia (AML), or T-cell acute lymphoblastic leukemia (T-ALL). Hematological neoplasms in carriers of a germline RUNX1 mutation need additional secondary mutations or chromosome aberrations to develop. If a disease-causing mutation is known in the family, it is important to prevent hematopoietic stem cell transplantation from a sibling or other relative carrying the familial mutation. First experiments introducing a wild-type copy of RUNX1 into induce pluripotent stem cells (iPSC) lines from patients with FPDMM appear to demonstrate that by gene correction reversal of the phenotype may be possible.